التصميم اإلانشائي المقترح لمدرسة دورا الصناعية - طنينة, محمد; الشلالفه, بلال; قباجه, سامر; طرايرة, روزان (جامعة بوليتكنك فلسطين - مباني, 2015)
تعتبر المدرسة بمثابة القلب العلمي والثقافي للمجتمع، فهي عبارة عن مركز الحياة الفكرية حيث تتدفق منها المعرفة إلى جمهور الطلبة. ومن هنا فإن التصميم المعماري بما يلبيه من احتياجات إنسانية مثل الديمومة الوظيفية، الجمال، االقتصاد تعتبر في غاية األهمية، كما أن الوصف المعماري يساعد بشكل كبير في فهم المشروع بشكل جيد. تتمثل فكرة هذا المشروع في التصميم اإلنشائي لمدرسة دورا الصناعية، التي تتكون من طابقين وتشمل على مسرح ومشاغل ومختبرات وغرف صفية وكافتيريا وغرف المدرسين، مدروسة من ناحية األبعاد واالرتفاعات والفراغات العمرانية 2 الصحيحة، مجموع المساحات الطابقية للمدرسة 6925 م . تم في هذا المشروع عمل دراسة تفصيلية وتحليل العناصر الهيكلية المشكلة لهذه المدرسة، واألحمال المتوقعة، وعمل التصاميم للعناصر المطلوبة وإعداد المخططات اإلنشائية لهذا البناء . تم تصميم المشروع باستخدام الكود األمريكي للتصميم ACI318-08 وكذلك الكود األردني لحساب األحمال الحية، باإلضافة الستخدام بعض البرامج مثل Office2010 ،Autocad2010، وكذلك برامج التصميم مثل Atir ، Etabs،Safe ...etc لعمل التصاميم والمخططات الالزمة إلنجاز المشروع. The school is a scientific and cultural heart of the community, it is a center of intellectual life where the knowledge flow to students public. Hence, and the architectural design of accountability, including humanitarian needs such as job permanence, beauty, the economy is considered very important, and the architectural descriptions significantly helps in the understanding of the project well. The idea of this project is the structural design of the Dura Industrial School, which consists of two floors and includes theater, workshops, laboratories, classrooms, a cafeteria and rooms of teachers. It is well thought out in terms of dimensions and elevations correct and urban spaces, the total floor area spaces for the school is 6925 m2 . In this project detailed study, analysis of structural elements problem consisting this school, and the expected loads will be prepared. In addition, the required element will be designed and the construction drawing to be prepard. The project was designed using the US code (ACI318-08 ) as well as the Jordanian code was used to calculate the live loads, as well as for the use of some programs such as Autocad2010, Office2010. In addition to using design programs such as Safe, Etabs, Atir …etc to prepare designs necessary to complete the project and drawings.
no of pages 100 , مباني 19/2015
Keywords: التصاميم الانشائية; المدارس الصناعية